Which aid initiatives strengthen food security? Lessons from Uttar Pradesh. Issue 2 (17th February 2017) - Petrikova, Ivica; Hudson, David
ABSTRACT: This study contributes to existing research on the relative effectiveness of aid initiatives in addressing food insecurity in India. Specifically, it compares the effects of crop, livestock, credit, and WASH interventions implemented by a development NGO with the impacts of a public direct-transfer scheme on food security among communities in Uttar Pradesh. The NGO's agricultural and WASH interventions and the government's Antyodaya ration-card scheme appear to have the largest positive influence. Their positive impact can be enhanced by the presence of good governance and by the simultaneous application of several beneficial initiatives.